Literature, political subjectivity and education. A Triad for Reflection - Moreno Mosquera, Emilce (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Reading literature affects the subjective dimension of students and teachers, as well as readers and writ ers, and configures itself differently, taking into account the assymetry between agents. This article re- views the relation between the reading of literature and political subjectivity in the educational context, taking into account the importance given to the school and university as scenarios for the education of citizens. We propose that literature contributes decisively to the political configuration of children and young adults; this implies providing them with tools for the exercise of power and specifically oriented pedagogical action. The theorists discussed are Ruíz and Prada (2012), Nussbaum (1995, 1997, 2001, 2005, 2010) and Ricoeur (1996).